A Study on Teacher’s Experiment and Students’ Development with Listing Technique (LT) in Writing EFL Class - Ika Apriani Fata; Usman Kasim; Dian Fajrina; Arief Darmawan (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
This paper reports a case study of students’ writing development at state junior high school in Indonesia. The common problems in writing are developing main ideas, vocabulary and grammar subsequently using listing technique is one of the ways to generate ideas. It develops and arranges students’ ideas well. The purpose of this study is to find out whether listing technique can improve students’ writing skill or not with quantitative design. There were 23 students as the sample in which design randomly. The instruments were test and lesson plan. There were two test; pre-test and post-test. The result of test found that there was significant difference of the students’ writing skill between pre-test and post-test after teaching by using listing technique. To prove the hypothesis, the writer used t-score formula. Based on data analysis t-score was 12.5, meanwhile t-table was 2.074. Also, listing technique could improve students’ ability of writing aspects. Therefore, the writer concluded that teaching writing descriptive text by using listing technique gave good effect for students’ writing skill and the ability in aspects of writing; content, vocabulary and grammar. Keywords: Developing writing skill, listing technique, EFLCopyright © 2015 by Al-Ta'lim All right reserved